The conribution of maximal force production to explosive movement among young collegiate athletes - Peterson, M. D.; Alvar, B. A.; Rhea, M. R. (The Journal of Strength and Conditioning Research, 2006)
Critical to multidimensional sport conditioning is a systematic knowledge of the interactions between fitness components, as well as the transference relationships to performance. The purpose of this investigation was to examine the relationships between lower body muscular strength and several fundamental explosive performance measures. Fifty-four men and women collegiate athletes were tested to determine (a) lower-body muscular strength (1 repetition maximum barbell back squat), (b) countermovement vertical jump height and peak power output, (c) standing broad jump distance, (d) agility (cone T-test time), (e) sprint acceleration (m[middle dot]s-2), and (f) sprint velocity (m[middle dot]s-1). Analyses were performed using Pearson r correlations to examine these relationships. Partial correlations tested for relationships between performance measures while controlling for muscular strength. T-tests were performed to assess the difference between men and women. Correlation data demonstrated that significant (p < 0.01) strong linear relationships were indicated between muscular strength and power, as well as every sport-performance field tests. However, when controlling for strength with partial correlation, each of these relationships appreciably diminished. Significant differences (p < 0.05) were found between men and women for each of the performance tests. Muscular strength, peak power output, vertical jumping ability, standing broad jump, agility, sprint acceleration, and sprint velocity were all shown to be very highly related. Further examination demonstrated that body mass-adjusted muscular strength is more highly related to performance measures than is absolute muscular strength. Current correlation data provide a quantified look at the interaction between muscular fitness components, as well as the transfer relationship to several athletic-specific performance measures.